Pengujian Eksperimen Pembuang Panas dan Aliran Udara Pada Berbagai Bentuk Heatsink - Masrianto, Zulqifli; Mangalla, Lukas Kano; Gunawan, Yuspian (Enthalpy : Jurnal Ilmiah Mahasiswa Teknik Mesin, 2021)
Heatsinks are widely used in heat exchangers to increase the rate of heat transfer between a surface and the working fluid. This study aims to determine the effect of surface shape and area, and air flow velocity  on  the  rate  of  heat  transfer of  the  three  different  heatsinks.  The  research  was  conducted experimentally  by  testing  three  forms  of  heatsinks  with  variations  in  air  flow  velocity  in  a  small windtunell. The windtunnel is equipped with test equipment such as a handheld wind meter, K-Type thermocouple and a stopwatch. The heating source for the three model heatsinks is an electric heater that can reach a heating temperature of 100oC. Air flow velocity is varied from 0.5 m/s, 1.0 m/s and 1.5 m/s. The results of this experiment show that the heat dissipation rate is directly correlated with the air flow velocity and the heat transfer surface area. At flow velocities of 0.5 m/s, 1.0 m/s and 1.5 m/s, the air temperature behind the heat sink (T2) is 62.8oC, 56.7 oC, and 52.4 oC, respectively. From the heat calculation results show that the shape of the heatsink -model 3- dissipates heat higher than others where the surface area is much larger. For a flow velocity of 0.5 m/s, the rate of heat dissipation generated in model 1, Model 2 and model 3 are 26875 J/s, 34449.01 J/s and 37686.19 J/s, respectively. Keywords: Heat dissipation, surface model, air flow and heatsink.